Synthesis of bis-quinoxaline derivatives using Tonsil clay as a catalyst - M. Badali; J. Khalafy; M. Aghazadeh; R. H. Prager (Bulletin of the Chemical Society of Ethiopia, 2016)
A convenient and efficient synthesis of new bis-quinoxaline is described, involving condensation of 1,2-diamines with 9-ethyl-3,6-di(1,2-dioxoethyl)carbazole in the presence of Tonsil clay, a readily available and inexpensive catalyst. The structures of all new products were identified by 1H-NMR, 13C-NMR and FT-IR spectral data and microanalysis. DOI: http://dx.doi.org/10.4314/bcse.v30i1.12